ANALISIS KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS VII SMP NEGERI 2 RANCAKALONG - Nanang Supriatna; Yusfita Yusuf (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the numeracy literacy skills of seventh-grade students at SMP Negeri 2 Rancakalong. Numeracy literacy is a fundamental skill necessary for understanding and applying mathematical concepts in daily life. This research uses a qualitative method with a descriptive approach. The research sample consists of 30 students selected through purposive sampling. Data were collected through a numeracy literacy test, which includes three main indicators: number understanding, data interpretation, and solving numerical problems. The results show that the majority of students fall into the